Public Understandings of the Definition and Determination of Death: A Scoping Review. Issue 5 (7th April 2022) - Zheng, Katina; Sutherland, Stephanie; Hornby, Laura; Shemie, Sam D.; Wilson, Lindsay; Sarti, Aimee J.
Abstract : Background: Advances in medicine and technology that have made it possible to support, repair, or replace failing organs challenge commonly held notions of life and death. The objective of this review is to develop a comprehensive description of the current understandings of the public regarding the meaning/definition and determination of death. Methods: This scoping review was conducted in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. Online databases were used to identify articles published from 2003 to 2021. Two reviewers (S.S. and K.Z.) screened the articles using predefined inclusion and exclusion criteria, extracted data for specific content variables, and performed descriptive examination. Complementary searches of reference lists complemented the final study selection. A search strategy using vocabulary of the respective databases was created, and criteria for the inclusion and exclusion of the articles were established. Results: Seven thousand four hundred twenty-eight references were identified. Sixty were retained for analysis, with 4 additional references added from complementary searches. A data extraction instrument was developed to iteratively chart the results. A qualitative approach was conducted to thematically analyze the data. Themes included public understanding/attitudes toward death and determination of death (neurological determination and cardiocirculatory determination of death), death and organ donation, public trust and legal variability, and media impacts. Conclusions: This review provides a current and comprehensive overview of the literature related to the general public's understanding and attitudes toward death and death determination and serves to highlight the gaps in this topic. Abstract :